The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1136/bmjopen-2016-013105
|View full text |Cite
|
Sign up to set email alerts
|

A cross–sectional study on the prevalence and associated risk factors for workplace violence against Chinese nurses

Abstract: ObjectivesThe purpose of the present study was to explore the characteristics of workplace violence that Chinese nurses at tertiary and county–level hospitals encountered in the 12 months from December 2014 to January 2016, to identify and analyse risk factors for workplace violence, and to establish the basis for future preventive strategies.DesignA cross–sectional study.SettingA total of 44 tertiary hospitals and 90 county–level hospitals in 16 provinces (municipalities or autonomous regions) in China.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
135
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(156 citation statements)
references
References 34 publications
14
135
5
2
Order By: Relevance
“…In another study, 106 of 840 general practitioners and nurses in Heilongjiang province (Northeast China) reported physical assault in the past 12 months, with 62.3% of the perpetrators being the patients’ relatives and 22.6% being the patients themselves 8. A most recent cross-sectional study with nurses (n=15, 970) in 44 tertiary hospitals and 90 county-level hospitals from 16 provinces in China reported that the prevalence of MWV was 65.8%, which including verbal violence (64.9%), physical violence (11.8%) and sexual harassment (3.9%) 9. One study conducted in Macau in 2014 showed that 18.1%, 56%, 14.5% and 4.7% of nurses (n=613) and 3.7%, 38.3%, 12.1% and 3.7% of doctors (n=107) experienced physical assault, verbal abuse, bullying, and sexual harassment in the preceding year, respectively 10.…”
Section: Mwv: Prevalence and Related Laws In Chinamentioning
confidence: 99%
“…In another study, 106 of 840 general practitioners and nurses in Heilongjiang province (Northeast China) reported physical assault in the past 12 months, with 62.3% of the perpetrators being the patients’ relatives and 22.6% being the patients themselves 8. A most recent cross-sectional study with nurses (n=15, 970) in 44 tertiary hospitals and 90 county-level hospitals from 16 provinces in China reported that the prevalence of MWV was 65.8%, which including verbal violence (64.9%), physical violence (11.8%) and sexual harassment (3.9%) 9. One study conducted in Macau in 2014 showed that 18.1%, 56%, 14.5% and 4.7% of nurses (n=613) and 3.7%, 38.3%, 12.1% and 3.7% of doctors (n=107) experienced physical assault, verbal abuse, bullying, and sexual harassment in the preceding year, respectively 10.…”
Section: Mwv: Prevalence and Related Laws In Chinamentioning
confidence: 99%
“…10,47 Individuals or gangs thriving on arm-twisting for reducing the health care costs and obtaining commission from the patients are known as -Yi Nao‖ in China (literally meaning hospitaldisturbance). 20,22,26,28 A 2006 survey of 270 tertiary hospitals reported that over 73% of the participating hospitals had experienced Yi Nao gangs which consist largely of unemployed people with a designated leader. These incidences had nearly doubled from 9831 in 2006 to 17,243 in 2010.…”
Section: Causesmentioning
confidence: 99%
“…Patients and their relatives may use illegal organizations in order to arm-twist the hospitals for compensation, rather than use the normal legal procedures. 26,28 Zero protection for doctors and lack of security provisions was yet another important concern. A descriptive cross sectional study on security related perceptions of HCPs in a district hospital of South Africa has highlighted the following causes of HCWPV: inadequate security staff, poorly equipped security personnel, deficient screening of visitors and lack of confidence in the capacity and ability of security staff to ensure a safe environment.…”
Section: Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalencias de violencia en el trabajo en dirección a los profesionales de enfermería de ambientes de emergencia también son frecuentemente registradas en la literatura (4,(19)(20) , así como el impacto de estos eventos a la salud de los trabajadores que fueron víctimas (21) . El estudio actual fortalece la relación entre violencia en el trabajo y aspectos de salud del trabajador al identificar que las víctimas presentaban número medio mayor de problemas de salud de lo que las no víctimas.…”
Section: Nº 51 Julio 2018unclassified